Unang siglo ng nobela sa Filipinas - Almario, Virgilio S. (Pasig City, Philippines Anvil Pub., 2009)
History of the novel in the Philippines.
At head of title: Panunuring pampanitikan.
highschool to college students
In Tagalog.